Altered native stability is the dominant basis for susceptibility of α(1)-antitrypsin mutants to polymerization - Irving, James A. (Portland Press Ltd., 2014)
Serpins are protease inhibitors whose most stable state is achieved upon transition of a central 5-stranded β-sheet to a 6-stranded form. Mutations, low pH, denaturants and elevated temperatures promote this transition, which can result in a growing polymer chain of inactive molecules. Different types of polymer are possible, but, experimentally only heat has been shown to generate polymers in vitro consistent with ex vivo pathological specimens. Many mutations that alter the rate of heat-induced polymerization have been described, but interpretation is problematic because discrimination is lacking between the effect of global changes in native stability and specific effects on structural mechanism. We show that the temperature midpoint (T(m)) of thermal denaturation reflects the transition of α(1)-antitrypsin to the polymerization intermediate, and determine the relationship with fixed-temperature polymerization half-times (t(0.5)) in the presence of stabilizing additives [TMAO (trimethylamine N-oxide), sucrose and sodium sulfate], point mutations and disulfide bonds. Combined with a retrospective analysis of 31 mutants characterized in the literature, the results of the present study show that global changes to native state stability are the predominant basis for the effects of mutations and osmolytes on heat-induced polymerization, summarized by the equation: ln(t(0.5,mutant)/t(0.5,wild-type))=0.34×ΔT(m). It is deviations from this relationship that hold key information about the polymerization process.